The Effect of Motor Balance Training on Some Motor - Sensory Abilities for fencing players - Farah Khaled Abdulah; Riad Khalil Kammas (College of Physical Education and Sport Sciences, 2020)
The research aim at deigning motor balance training as well as finding its effect on time perception in fencing skills specially lounges parry and repose. The problem of the research lies in the lack of such studies that concentrate on goof motor balance in fencing. The subjects were (8) league fencers. The training program consisted of 18 training sessions. The data was collected and treated using proper statistical methods to come up with the conclusions.